Identidade e pertencimento étnico-racial: processos de construção e reconhecimento - Silva, Lilian Fernandes (2022)
The research has as its object the processes of construction and recognition of identity and ethnic-racial belonging of black women and their development in the current historical context, especially in situations marked by racial and sexist tensions. The problem of the study is to unravel the implications of the ideology of whitening, the myth of racial democracy and meritocracy that hide structural racism and compromise the recognition and acceptance of individuals about their own ethnic-racial identity and belonging. Considering the social relationship between sex, race-ethnicity and class. The general objective of the research is to know the processes of construction and recognition of identity and ethnic-racial belonging of black women in contemporary times: what aspects influence and what impacts it produces. The specific objectives are: to identify the subjective and socio-historical dimensions that permeate the construction of identity and ethnic-racial belonging in Brazil; the presentation of the profile of black women from the survey and analysis of social indicators and the unveiling of the processes of construction and recognition of identity and ethnic-racial belonging today, from the perspective of women who declare themselves and/or are declared black, make up the working class, inhabit the peripheral territories of the metropolitan region of São Paulo and are linked or not to black social movements. The quantitative-qualitative research has an exploratory character and will be carried out through bibliographic, documental and oral source studies